The Role of Blockchain Technology in Increasing Transparency and Security of Financial Management in the Banking Sector - Rustam, Andi; Hasanah, Nuramalia; Pasaribu, Hiras; Aina, Qorri; Judijanto, Loso (Journal of Ecohumanism, 2025)
This article discusses the role of blockchain technology in improving the transparency and security of financial management in the banking sector. This study uses a qualitative approach with a literature study method to analyze various references related to the application of blockchain in the banking world, both in terms of theory, policy, and practice. Blockchain, as a decentralized technology that allows for transparent and secure recording of transactions, has great potential to revolutionize the way banks manage financial data and interact with clients and other financial institutions. Through literature analysis, the study identified the key advantages of blockchain, such as reduced fraud risk, increased transaction efficiency, and enhanced data integrity. In addition, the study also discusses the challenges faced by the banking sector in implementing blockchain, including regulatory issues, technological infrastructure, and resistance to change from related parties. By reviewing various case studies of blockchain implementation in leading banks, this article shows how this technology can be used to increase public trust in the financial system. The study concludes that, despite the great challenges that remain, blockchain can play a significant role in strengthening security and transparency in financial management, thereby supporting the creation of a more efficient and accountable banking system in the future.